PERANCANGAN KAWASAN GELANGGANG OLAHRAGA DI KOTA SEKADAU - Gustiawan Hidayat; Valentinus Pebriano; Lestari Lestari (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2022)
The sports arena is a place to do sports activities. The existence of the arena has an important role so that the goals of exercise can be achieved. In Sekadau Regency at this time the place is still not available, so that services for the community in Sekadau Regency have not been fulfilled to the fullest. Meeting the needs of community infrastructure services and improving human quality is one of the goals of designing the arena building. The existence of a sports arena in Sekadau Regency not only supports the community in exercising, but can be used outside of sports activities. The sports arena has more than one activity that is accommodated so that it has the potential to become a center for gathering public activities and becoming an icon of the city. The design of the sports arena area aims to facilitate sports activities, public spaces and become an icon of Sekadau City. In this design the glass box method is used to support the design objectives. The results of the design of the sports arena area in the form of areas and buildings that elevate locality values, form an area and building design that displays characteristics and is only found in Sekadau City.